The Renaissance of Remote Places MATILDE Manifesto - Membretti, Andrea; Dax, Thomas; Krasteva, Anna (Routledge Studies on Remote Places and Remoteness, 2022)
With a particular attention to remote places and marginalised territories, this book provides a conceptualisation of the role of internal and international migration to the local development and resilience of the rural and mountain regions of Europe. The book is a collective effort produced by the international and multi-disciplinary network of the Horizon 2020 project MATILDE. In declaring a public and trans-regional position - in the form of a Manifesto for the renaissance of remote places - the book contributes to a new narrative about migration and rural/mountain territories for the future of the entire continent. Mobilizing new data and scientific-based information, the book calls for putting remote regions and their inhabitants at the core of innovative policies at local, regional, national and EU levels. An important resource for researchers, students and policymakers in human and population geography, rural studies, migration studies, social and political sciences.